Evaluation of Mental Load of Drivers in Long Highway Tunnel Based on Electroencephalograph - Yang, Yanqun; Feng, Yang; Easa, Said M.; Zheng, Xinyi (Frontiers in Psychology, 2021)
In recent years, the mileage of tunnels has substantially increased with the rapid highway construction, which has led to increasing accidents in highway tunnels. Most studies on tunnel accidents have mainly focused on the external environment, such as tunnel structure, traffic volume, and lighting, while studies on driver mental state in the tunnels has been relatively limited. In this paper, three driving scenarios with different front vehicle speeds (60 km/h, 45 km/h, and 30 km/h) were setup in a driving simulation experiment, involving 24 drivers. The electroencephalogram (EEG) technology was used to collect the main EEG indicators during the driving simulation of the scenarios: α, β, and θ waves and the wave ratio, (α + θ) / β. According to the measurement of β wave, after adapting to the tunnel environment, the driver alert level was the lowest, which showed that that the drivers were most comfortable at the speed of 45 km/h. The conclusion of the study provided a guideline for the recommended speed limit in the tunnel.